Brief Report: Polymorphisms in CAMKK2 may Influence Domain-Specific Neurocognitive Function in HIV+ Indonesians Receiving ART. (1st January 2022) - Gaff, Jessica; Estiasari, Riwanti; Diafiri, Dinda; Halstrom, Samuel; Kamerman, Peter; Price, Patricia
Abstract : Background: Despite effective antiretroviral therapy (ART), milder forms of HIV-associated neurocognitive disorders remain prevalent and are characterized by neuroinflammation, synaptic dysfunction, and neuronal loss. Methods: We explore associations between neurocognitive impairment in HIV+ Indonesians and 17 polymorphisms in adjacent genes involved in inflammation and neuronal growth/repair pathways, P2X4R and CAMKK2 . HIV+ Indonesians (n = 59) who had received ART for 12 months were assessed to derive Z-scores for the attention, fluency, memory, executive, and motor speed domains relative to local control subjects. These were used to determine total cognitive scores. Results: No alleles of P2X4R displayed significant associations with neurocognition in bivariate or multivariable analyses. In CAMKK2, rs2686344 influenced total cognitive scores in bivariate analyses ( P = 0.04). Multivariable linear regression modeling independently associated rs2686344 with higher executive function Z-scores ( P = 0.05) after adjusting for CD4 T-cell counts (adjusted R 2 = 0.103, model P = 0.034), whereas rs1653588 associated with lower and rs1718120 ( P = 0.05) with higher fluency Z-scores ( P = 0.05) after adjusting for education and log10 HIV RNA copies/mL (adjusted R 2 = 0.268, model P = 0.001). Conclusions: Polymorphisms in CAMKK2 may influence neurocognitive outcomes in specific domains in HIV+ Indonesians receiving ART for 12 months. Abstract : Supplemental Digital Content is Available in the Text.